2010
DOI: 10.1002/jcb.22716
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Proliferative Effects of Evodiamine on Human Thyroid Cancer Cell Line ARO

Abstract: The incidence of thyroid cancer increases with age, and it is twice in women as common as in men. The undifferentiated thyroid cancer (UTC) is the most aggressive of all thyroid cancers. Unfortunately, there are almost no efficacious therapeutic modalities. It is important to develop some new effective therapies. Evodiamine is a chemical extracted from a kind of Chinese herb named Wu-Chu-Yu and has been demonstrated to be effective in preventing the growth of a variety of cancer cells. In the present study, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 40 publications
2
44
0
Order By: Relevance
“…In addition, Takada et al found that EVO exerts apoptotic activity by regulating NF-κB activation, resulting in the inhibition of NF-κB-controlled downstream genes, including cyclin D1, c-Myc, survivin, X chromosome-linked IAP (XIAP), Bcl-2 and Bcl-Xl (43). Numerous experiments have demonstrated that EVO activated initiator caspases (caspase-8 and 9) and/or effector caspases (caspase-3) to induce the apoptosis in a variety of tumor cell lines including human colorectal carcinoma COLO205 and HT-29 cells (44) and human thyroid cancer cell line ARO (45). In addition, another study showed that EVO promoted translocation of apoptosis-inducing factor (AIF) into the nucleus of human leukemia u937 cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Takada et al found that EVO exerts apoptotic activity by regulating NF-κB activation, resulting in the inhibition of NF-κB-controlled downstream genes, including cyclin D1, c-Myc, survivin, X chromosome-linked IAP (XIAP), Bcl-2 and Bcl-Xl (43). Numerous experiments have demonstrated that EVO activated initiator caspases (caspase-8 and 9) and/or effector caspases (caspase-3) to induce the apoptosis in a variety of tumor cell lines including human colorectal carcinoma COLO205 and HT-29 cells (44) and human thyroid cancer cell line ARO (45). In addition, another study showed that EVO promoted translocation of apoptosis-inducing factor (AIF) into the nucleus of human leukemia u937 cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…Evodiamine was identified as one of the major active substances of Evodia rutaecarpa (5,9). Previous studies have reported the antitumor activity of evodiamine; one study demonstrated that evodiamine was able to inhibit proliferation of human thyroid cancer cells through cell cycle arrest at M phase and the induction of apoptosis (10). In addition, evodiamine was found to inhibit the growth of prostate cancer cells via the induction of apoptosis (11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that EVO possessed a plenty of pharmacologic activities, such as anti-obesity, anti-inflammatory , and anti-infectious effect (Li-Weber, 2013;Yu et al, 2013). Furthermore, many studies declared that EVO was a promising anti-tumor agent (Jiang & Hu, 2009), which could suppress proliferation (Chen et al, 2010), induce apoptosis (Rasul et al, 2012), and inhibit metastasis (Takada et al, 2005) of cancer cells. These capabilities were believed to function well through the effects of EVO, which could alter the balance of Bcl2 and Bax gene expression by the caspase pathway in cancer cells (Fei et al, 2003).…”
Section: Introductionmentioning
confidence: 99%